Effect of Various Cultural Operations with or without Seeding and Fertiliser, on Grassland Development in Ravine Lands - Singh, Bakhshish; Majumdar, S. K.; Verma, Balvir (Indian Forester, 1968)
Four cultural operations (C1-Control, C2-Harrowing, C3-Ploughing, and C4-Furrowing at 1 m interval and three seeding and fertiliser treatments (S0f0 - no seeding or fertiliser, S1f0-seeding with a mixture of Cenchrus ciliaris and Dicanthium annulatum at 6 kg/ha; and S1f1-seeding as above and fertiliser application at 20 kg N, 20 kg P2O5 per ha) were tried in a split plot design with 4 replications to study their effects, singly and in combination with each other, on the various aspects of grassland production in the Ravine Lands at the Soil Conservation Research Station, Vasad (Gujarat). Results indicate that ploughing gave significantly higher forage production than all other cultural operations tried, but reduced the basal cover per cent of the grasses to a considerable extent. Furrowing was better than Harrowing in overall performance. Out of the two grass species used for seeding, Cenchrus ciliaris developed higher percentage composition in the stand. Both the seeding treatments, i.e., seeding only and seeding with fertilisers increased the forage yield, height growth and percentage composition (of the two species used for seeding), but reduced the basal cover per cent and number of tillers per clump. Furrowing combined with seeding of Cenchrus ciliaris has been found to be a comparatively suitable practice for grassland development on marginal lands and humps of ravine areas in this region.